2021
DOI: 10.1242/jcs.258579
|View full text |Cite
|
Sign up to set email alerts
|

S-acylation of Orai1 regulates store-operated Ca2+ entry

Abstract: Store-operated Ca2+ entry is a central component of intracellular Ca2+ signaling pathways. The Ca2+ release-activated channel (CRAC) mediates store-operated Ca2+ entry in many different cell types. The CRAC channel is composed of the plasma membrane (PM)-localized Orai1 channel and endoplasmic reticulum (ER)-localized STIM1 Ca2+ sensor. Upon ER Ca2+ store depletion, Orai1 and STIM1 form complexes at ER–PM junctions, leading to the formation of activated CRAC channels. Although the importance of CRAC channels i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 44 publications
10
20
0
Order By: Relevance
“…ORAI1 PM clusters are the macroscopic signature of ORAI1 trapping by STIM1, a dynamic event involving the entry and exit of ORAI1 particles into PM domains facing STIM1 molecules on apposed cortical ER cisternae Wu et al, 2014 . The reduced presence of ORAI1-C143A in puncta is consistent with a recent report that S-acylation is required for the recruitment of active ORAI1 channels to STIM1 clusters West et al, 2022 . Reduced ORAI1 trapping by STIM1 would reduce CRAC currents and possibly FCDI by increasing the amount of STIM1 molecules required to trap and gate deacylated channels.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…ORAI1 PM clusters are the macroscopic signature of ORAI1 trapping by STIM1, a dynamic event involving the entry and exit of ORAI1 particles into PM domains facing STIM1 molecules on apposed cortical ER cisternae Wu et al, 2014 . The reduced presence of ORAI1-C143A in puncta is consistent with a recent report that S-acylation is required for the recruitment of active ORAI1 channels to STIM1 clusters West et al, 2022 . Reduced ORAI1 trapping by STIM1 would reduce CRAC currents and possibly FCDI by increasing the amount of STIM1 molecules required to trap and gate deacylated channels.…”
Section: Discussionsupporting
confidence: 91%
“…A comparable inhibition was observed with cysteine-less ORAI1 in an earlier study focusing on Cys195 substitutions that prevent I CRAC inhibition by hydrogen peroxide Bogeski et al, 2010 . These data indicate that the ORAI1 channel is S-acylated at Cys143 and that replacement of this residue, but not of the two other ORAI1 cysteines, prevents S-acylation and impacts channel function, consistent with the recent report that Orai1 is rapidly S-acylated at cysteine 143 upon ER Ca 2+ store depletion West et al, 2022 . Cys143 is the only cysteine conserved in all human isoforms and in ORAI1 homologs up to C. elegans , suggesting that S-acylation at this site is an evolutionary conserved function.…”
Section: Discussionsupporting
confidence: 89%
“…This hypothesis is supported by our findings that both Orai1 and STIM1 reach peak S-acylation levels at the same time point after T cell stimulation (Fig. 1B-C; (11)). Similarly, we have observed in TIRF time lapse imaging experiments that the peak colocalization of Orai1 and STIM1 happens approximately at the same time after store depletion (Fig.…”
Section: Discussionsupporting
confidence: 83%
“…STIM1 can bind phosphatidylinositol 4,5-bisphosphate (PIP 2 ) via a lysine-rich C-terminal domain, and studies have shown that STIM1 translocates and binds PIP 2 present specifically in lipid rafts (10). This indicates an active mechanism for targeting STIM1 to lipid rafts, as we and others have shown previously for Orai1 (11,12). Perhaps not surprising, it has also been shown that there is reduced mobility of Orai1 and STIM1 after store depletion at ER-PM contact sites (13,14).…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation